Sociocultural Determinants of Clinical Autopsy Refusal and Their Medicolegal Impact on Diagnostic Accuracy in Indonesian Tertiary Hospitals - Yuniarti Maretha Pasaribu; Riri Arisanty Syafril Lubis; Franklin Shane; Lisye Tiur Simanjuntak (Sriwijaya Journal of Forensic and Medicolegal, 2025)
Introduction: Clinical autopsy refusal remains a critical barrier to diagnostic quality assurance and medicolegal accountability in Indonesian hospital medicine. This retrospective cohort study enrolled 324 consecutive inpatient deaths across three tertiary referral hospitals in Palembang, South Sumatra (January 2019 – December 2023), to characterize sociocultural determinants of autopsy refusal and their impact on diagnostic accuracy and time-to-correct-diagnosis. Methods: The primary outcome was next-of-kin refusal of clinical autopsy consent; secondary outcomes included diagnostic discrepancy classified by the Goldman system, and time-to-correct-diagnosis analyzed by Kaplan-Meier survival analysis with log-rank testing. Multivariate logistic regression with bootstrap-derived confidence intervals identified independent predictors of refusal. Results: The overall autopsy refusal rate was 84.0% (272/324). Independent predictors were Javanese ethnicity (OR 3.64, 95% CI 1.77–7.48; p<0.001), Islamic religious affiliation (OR 2.49, 95% CI 1.42–4.37; p=0.001), primary or no formal education (OR 2.36, 95% CI 1.19–4.68; p=0.014), age per 10-year increment (OR 1.18, 95% CI 1.05–1.33; p=0.006), and low household income below 2 million IDR (OR 1.76, 95% CI 1.00–3.10; p=0.049). The model demonstrated good discrimination (C-statistic 0.81) and calibration (Hosmer-Lemeshow p=0.43). Major diagnostic discrepancy (Goldman Class I–II) occurred in 26.1% of the refused cohort versus 13.5% in the consented cohort (p=0.047). Median time-to-correct-diagnosis was 19 days (95% CI 15–24) in the refused group versus 5 days (95% CI 3–8) in the consented group (log-rank p<0.001). Conclusion: These findings provide robust evidence for the medicolegal urgency of addressing sociocultural barriers to autopsy consent through culturally sensitive policy reform in Indonesia.